Content: Evolution & Development 1/2016. Issue 1 (13th January 2016) - Unknown
Abstract : Cover image: Micrograph from one of Joseph‐Peter Weinmann's original 3x4 inch celloidin slides of the human periodontal ligament that the Viennese scholars brought from Vienna to Chicago. These 20 micron thick sections cut with a sledge microtome were a unique exemplar of the Viennese art of hard‐tissue histology. The micrograph illustrates the continuous growth of human cementum as illustrated by prominent growth lines, the tooth root, and the position of Malassez rests in the center of the periodontal region. The cement rings are in the center, including a polychromatic region; while root dentin (left side) and alveolar bone (right side) are at the respective margins of the image.